Implementasi Opencart Sebagai Solusi Penjualan Digital untuk Home Industry di Kabupaten Dharmasraya - Pratiwi, Erwita; Annas, Firdaus; Deqa Annisa G, Puti (JOVISHE : Journal of Visionary Sharia Economy, 2023)
Home industries in Dharmasraya Regency face significant challenges in marketing and increasing product sales, most of which still rely on conventional methods such as direct sales and regular customer relations. The lack of utilization of digital technology leads to narrow market reach and stagnant sales growth. This condition urgently requires an effective and efficient digital solution to support sales transformation. This research aims to implement a sales system based on the OpenCart platform as a strategic step in digitizing home industry MSMEs in Dharmasraya Regency. The methodology used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Research data was obtained through a survey of MSME players to identify needs, key challenges, and user preferences for digital platforms. The OpenCart-based system design includes product management features, online payment integration, and flexible inventory settings. The results show that the implementation of the OpenCart-based system has a positive impact on MSME operations. The system improves efficiency in sales management and expands market reach through optimizing e-commerce platforms. Increased customer accessibility to MSME products and ease of online transactions are among the main advantages of this system. The implications of this research emphasize the importance of digital technology adoption in strengthening the competitiveness of MSMEs, especially in rural areas such as Dharmasraya Regency. OpenCart-based digitalization can be a practical and relevant implementation model to encourage the growth of MSMEs in the digital economy era.